Acute effects of partial positive allosteric GABAA receptor modulation by GT-002 on psychophysiological and cognitive measures: protocol for the TOTEMS phase II trial targeting cognitive impairment associated with schizophrenia - Siebner, Thomas Hartwig; Ambrosen, Karen Sandø; Lemvigh, Cecilie Koldbæk; Ryan, Christine Natasha; Sørensen, Mikkel Erlang; Hernández-Lorca, María; Glenthøj, Birte Yding; Larsen, Kit Melissa; Witt, Michael-Robin; Oranje, Bob; Ebdrup, Bjørn Hylsebeck (Frontiers in Psychiatry, 2025)
BackgroundCognitive impairment remains a critical unmet treatment need in schizophrenia spectrum disorders (SSD). Disruption of cortical excitation/inhibition balance, involving dysfunction of the gamma-aminobutyric acid (GABA) system, leads to aberrant gamma oscillations and impaired brain network function. This disruption may manifest as hypofrontality, which is associated with deficits in basic information processing thought to underlie the cognitive impairments observed in SSD. GT-002 is a novel GABAA receptor partial positive allosteric modulator. Preclinical rodent studies have demonstrated GT-002’s potential to reduce hypofrontality, while three Phase I trials have established its safety and tolerability in healthy participants.AimThe TOTEMS Phase II trial examines acute effects of a single oral dose of GT-002 on psychophysiological measures of early information processing, including event-related electroencephalography (EEG), electromyography, and resting-state EEG in SSD patients.MethodsA single-center, double-blind, placebo- and active comparator-controlled, randomized, four-way crossover challenge trial. We will recruit 20 clinically stable patients with SSD and 30 healthy controls. Participants will receive a single dose of GT-002 (1 mg and 2 mg, developed by Gabather AB), oxazepam (15 mg), and placebo across four study drug exposure days, separated by a washout period ≥7 days. Psychophysiological measures and cognitive assessments, including the Trail Making Test and selected subtests from the Brief Assessment of Cognition in Schizophrenia and Cambridge Neuropsychological Test Automated Battery, will be conducted following each administration.Anticipated resultsWe hypothesize that GT-002 will improve prepulse inhibition of the startle reflex in patients relative to placebo and oxazepam, reflecting improved sensorimotor gating. Secondary hypotheses include improved mismatch negativity, selective attention, 40-Hz auditory steady-state response, and normalized resting-state EEG in SSD patients following GT-002. Exploratory endpoints include safety and tolerability of GT-002 as well as differential effects on cognition compared to oxazepam, particularly in processing speed, attention, reaction time, and working memory.PerspectivesTOTEMS is the first trial to investigate acute effects of GABAA receptor modulation by GT-002 on early information processing in SSD. If successful, it will support further clinical trials of longer-term GT-002 treatment as a novel pharmacological approach to target impairments in information processing in SSD, potentially ameliorating cognitive impairments.Clinical trial registrationEU CT number 2024-519389-28-00.